The Effect of Beauveria bassiana on the Development of Bactrocera dorsalis Complex at Various Soil Depths (Biosaintifika: Journal of Biology & Biology Education, 2026)
Bactrocera dorsalis complex is a pest that causes losses in agriculture because it causes damage and rotting of fruits and vegetables. Beauveria bassiana is an entomopathogenic fungus that produces secondary metabolites that can infect pests. This study aimed to determine the effect of B. bassiana on the growth of B. dorsalis complex at different soil depths. This study adopted a randomized factorial design with two factors. The first factor was treatment, which consisted of control, water addition, and Streptomyces sp. application. The second factor was soil depth, consisting of eight pupation depth treatments of 0, 4, 10, 20, 30, 40, 50, and 60 cm. The pupae were placed in a mica tube with a diameter of 5 cm and covered with sieved soil. Replication was carried out four times. The observed parameters included dead pupae, successful imago, normality, and development time. B. bassiana treatment significantly increased pupal mortality, decreased successful survival, and the normality of the imago. B. bassiana treatment also significantly extended the development time of all imago parameters. Soil depth significantly affected pupal mortality and all imago parameters. Soil depth significantly affected the development time of successful imagoes, but not the development time of normal and abnormal imagoes. These findings suggest that B. bassiana effectively controls fruit fly pupae in soils of varying depths. This study provides a foundation for integrating entomopathogenic B. bassiana into fruit fly control strategies targeting the pupal stage. This research supports SDGs Zero Hunger because the result directly contributes to sustainable agriculture through biological control of the fruit fly (Bactrocera dorsalis), a major pest of horticultural crops, reduced crop losses, and increased agricultural productivity, as well as provides an environmentally friendly alternative to chemical pesticides.